HATCH score associated with new-onset atrial fibrillation in patients with ST-segment elevation myocardial infarction - Shan Qin; Yexiao Tao; Chenzhe Tang; Qi Zhang; Yong Li; Zhengdong Fei (BMC Cardiovascular Disorders)
Abstract Background The HATCH score, a new atrial fibrillation (AF) risk model, has drawn wide attention. However, in patients with ST-segment elevation myocardial infarction (STEMI), the relationship between the HATCH score and NOAF remains unclear. This study aimed to assess the association between HATCH score and new-onset AF (NOAF) after percutaneous coronary intervention (PCI) in STEMI patients. Methods This single-center retrospective observation consecutively selected patients diagnosed with STEMI who underwent primary PCI. All patients received continuous electrocardiogram monitoring during hospitalization (≥ 36 h). HATCH score was calculated based on hypertension (1 point), age > 75 years (1 point), stroke or TIA (2 point), COPD (1 point), and HF (2 point). Results A total of 774 patients were included in this study, of whom 65.37% were male, with a mean age of 63.53 ± 13.11 years, 73 patients (9.43%) developed NOAF. ROC curve demonstrated that the AUC of the HATCH score was 0.731, the cut - off value was 2.5. Multivariate logistic regression analysis indicated that the HATCH score (OR = 1.66, 95% CI: 1.41–1.95, P < 0.001) or HATCH score ≥ 3 (OR = 4.10, 95% CI: 2.39–7.02, P < 0.001) was an independent risk predictor for NOAF. The RCS analysis revealed a linear correlation between the HATCH score and NOAF (P for overall < 0.001). Conclusions Elevated HATCH score is an independent risk factor for the development of NOAF after PCI in STEMI patients. There was a linear dose-response relationship between HATCH score and NOAF.